Effect of microwave assisted blanching on the ascorbic acid oxidase inactivation and vitamin C degradation in frozen mangoes. (August 2018) - Xanthakis, Epameinondas; Gogou, Eleni; Taoukis, Petros; Ahrné, Lilia
Abstract: The effect of microwave assisted and conventional water blanching of mango ( Mangifera indica ) under two different blanching scenarios, High Temperature Short Time (HTST) and Low Temperature Long Time (LTLT) on ascorbic acid oxidase (AAO) inactivation and on vitamin C (l -ascorbic acid & dehydroascorbic acid) retention were comparatively studied. The impact of alternative blanching processes and subsequent frozen storage on enzymatic inactivation and vitamin C was kinetically modelled. Both water and microwave HTST as well as LTLT microwave treatments of mango pieces showed high degree of AAO inactivation. An approximately 30% residual AAO activity was observed and was described through a first order fractional conversion model. Microwave assisted blanching led to higher retention of total vitamin C in both LTLT and HTST treatments. In LTLT water blanching, vitamin C loss was mainly caused by mass transfer phenomena rather than temperature degradation, while after HTST treatments the decrease of total vitamin C content seemed to be mainly related to thermal degradation than due to the leakage of the nutrients in the blanching medium. Further inactivation of the thermostable fraction of AAO and degradation of total vitamin C were observed after frozen storage for 130 days at −18.63 ± 0.48 °C. Highlights: Microwave blanching was more efficient in terms of AAO inactivation in mango. Microwave blanching led to higher vitamin C retention compared to water blanching. AAO inactivation followed a first order fractional conversion kinetic model. Frozen storage followed by further AAO inactivation and vitamin C degradation.